“Constant dropping wears away a stone”: Chinese international women instructors’ duoethnography on advancing racial equity - Wang, P.; Huang, T. (International Journal of Qualitative Studies in Education, 2024)
Faculty of color are constantly experiencing trauma and racial inequities in inherently Eurocentric educational spaces where their histories, knowledge, and experiences are delegitimized and marginalized. Employing critical race feminism (CRF) and White racial identity development model, this article details ways in which two Chinese international women instructors grappled with tensions and trauma and celebrated (small) joys and successes within Predominantly White Institutions (PWI) in the United States. We drew on duoethnography, a dialogic methodological approach grounded in social justice, to make meaning of, (re)construct, and advance racial equity in pedagogy. We examined and analyzed four sources of data: our personal narratives, transcripts of eight Zoom meetings, reflection journals, and informal conversational exchanges. We identified three strategies for navigating dissonance and conflicts: 1) being vulnerable, 2) recognizing shared and differing marginalization or privileges, and 3) building allies intentionally and strategically. © 2024 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Chinese international women instructors of color; dept.cur; duoethnography; peer-reviewed; racial equity